Gastric emptying of non digestible solid radiopaque markers and autonomic neuropathy in chronic liver disease - A. Kemal GÜRBÜZ,; Levent DEMİRTÜRK,; Selahattin HÜLAGÜ,; E. KIZILKAYA,; S. GÜL,; E. KOÇER,; M. DANACI,; Z. ÇANKIR, (Turkish Journal of Gastroenterology, 2020)
-